Research advances of glycogen synthetic kinase-3β in diabetic nephropathy - He Zhi-xiu; Ma Chan-juan (Linchuang shenzangbing zazhi)
The pathogenesis of diabetic kidney disease（DKD）is rather complicated.And glycogen synthase-3 plays important roles in many signaling pathways in body.For chronic kidney injury caused by diabetes, it is involved in the damage process of glomerular podocytes, mesangial cells and renal tubular epithelial cells.This review discussed the expression and mechanism of glycogen synthesis kinase-3β in DKD.